2019
DOI: 10.1080/14766086.2019.1570474
|View full text |Cite
|
Sign up to set email alerts
|

The material nature of spirituality in the small business workplace: from transcendent ethical values to immanent ethical actions

Abstract: We interviewed leaders of small businesses who have integrated spirituality from diverse spiritual traditions into their workplaces. We contribute to a better understanding of the motives and deeply held values behind the integration of spirituality in the small business workplace, of how spiritual values and meaning are manifest in small business, and of how spirituality can be integrated into small business processes and behaviors. We build upon previous theoretical development of an authentically and spirit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
(47 reference statements)
1
31
0
Order By: Relevance
“…High religious increase one's motivation in living life. Driscoll et al (2019) revealed that spirituality is related to ethical and socially responsible actions. Entrepreneurs who have high spirituality try to maintain their companies to help employees.…”
Section: Effects Of Muslim Religiosity On Firm Survivalmentioning
confidence: 99%
“…High religious increase one's motivation in living life. Driscoll et al (2019) revealed that spirituality is related to ethical and socially responsible actions. Entrepreneurs who have high spirituality try to maintain their companies to help employees.…”
Section: Effects Of Muslim Religiosity On Firm Survivalmentioning
confidence: 99%
“…Many cross-cultural studies comparing the relationship between religiosity and ethical attitude in different countries, considering demographic factors like gender, age, and education have been also conducted (Small, 1992;McGee et al, 2015;Haloub et al, 2016;Grunbaum, 1997). Religious values help in institutionalising workplace spirituality and integrating ethical and socially responsible behaviour in organisations (Driscoll et al, 2019). Religious values play a significant role in defining work behaviour (Adnan et al, 2019) and organisational culture (Astrachan et al, 2020).…”
Section: Religiosity and Ethical Attitude Towards Businessmentioning
confidence: 99%
“…However, for both the Faith-Avoiding and Faith-Safe organizations, aiming for eudaimonic ends is unlikely to involve overt spiritual aspects, or be sourced in spiritual motivations (Guillén et al 2015). The other two organizational types aim at these 'goods of excellence' (Arjoon et al 2015) because spiritual beliefs and values are embedded in their organizational identity and culture, and in the practices of their leadership and employees (Delbecq 1999;Danyluk 2002;Fry and Nisiewicz 2013;Dyck 2017;Driscoll et al 2019).…”
Section: What Does This Mean For Christian Saw?mentioning
confidence: 99%